The structure of a glycogen phosphorylase glucopyranose spirohydantoin complex at 1.8 A resolution and 100 K: the role of the water structure and its contribution to binding. - Gregoriou, M; Noble, M; Watson, K; Garman, E; Krulle, T; de la Fuente, C; Fleet, G; Oikonomakos, N; Johnson, L (1998)
A glucopyranose spirohydantoin (a pyranose analogue of the potent herbicide, hydantocidin) has been identified as the highest affinity glucose analogue inhibitor of glycogen phosphorylase b (GPb). In order to elucidate the structural features that contribute to the binding, the structures of GPb in the native T state conformation and in complex with glucopyranose spirohydantoin have been determined at 100 K to 2.0 A and 1.8 A resolution, respectively, and refined to crystallographic R values of 0.197 (R[free] 0.248) and 0.182 (R[free] 0.229), respectively. The low temperature structure of GPb is almost identical to that of the previously determined room temperature structure, apart from a decrease in overall atomic temperature factors ((B) room temperature GPb = 34.9 A2; (B) 100 K GPb = 23.4 A2). The glucopyranose spirohydantoin inhibitor (Ki = 3.0 microM) binds at the catalytic site and induces small changes in two key regions of the protein: the 280s loop (residues 281-286) that results in a decrease in mobility of this region, and the 380s loop (residues 377-385) that undergoes more significant shifts in order to optimize contact to the ligand. The hydantoin group, that is responsible for increasing the affinity of the glucose compound by a factor of 10(3), makes only one hydrogen bond to the protein, from one of its NH groups to the main chain oxygen of His377. The other polar groups of the hydantoin group form hydrogen bonds to five water molecules. These waters are involved in extensive networks of hydrogen bonds and appear to be an integral part of the protein structure. Analysis of the water structure at the catalytic site of the native enzyme, shows that five waters are displaced by ligand binding and that there is a significant decrease in mobility of the remaining waters on formation of the GPb-hydantoin complex. The ability of the inhibitor to exploit existing waters, to displace waters and to recruit new waters appears to be important for the high affinity of the inhibitor.